Twórczość Borysa Pasternaka w badaniach polskich - Zbyrowski, Zygmunt (Studia Rossica Posnaniensia, 2011)
The Poetry of Boris Pasternak has been known in Poland thanks to translations and critical articles already since 1920s. Nonetheless Polish researchers became interested in his oeuvre as whole after the authors death. The largest number of studies originates from the last two decades, and their characteristic features include a great diversity of problems and methodology. The Polish authors are especially interested in the contents and form of Pasternak’s writings, and their analysis concern particular works (e.g. poems) or asserted questions and phenomena typical for Pasternak. The most active researchers in Poland are Anna Majmieskułow, Jerzy Faryno and Zygmunt Zbyrowski, other authors have published pertinent articles.